Prevalence and molecular characterization of Listeria spp. and Listeria monocytogenes isolated from fish, shrimp, and cooked ready-to-eat (RTE) aquatic products in Iran. (November 2016) - Abdollahzadeh, Esmail; Ojagh, Seyed Mahdi; Hosseini, Hedayat; Irajian, Gholamreza; Ghaemi, Ezzat Allah
Abstract: The prevalence of Listeria spp. and Listeria monocytogenes was investigated by biochemical and molecular methods in a total of 201 fish, shrimp, and ready-to-eat seafood samples collected from Iranian supermarkets. Thirty-six samples were also collected from a seafood processing plant. Twenty-one (8.86%) of the total retail and processing plant samples (237) were positive for Listeria spp., confirmed by a simplex PCR assay for the prs gene. Seven (2.95%) of the total samples were also positive for L. monocytogenes . The presence of four virulence-associated genes in the seafood isolates ( inlA, inlC, inlJ, and hlyA ) was examined using PCR and the results were compared with seven clinical L. monocytogenes strains. All virulence genes were detected in six fish isolates. One fish isolate did not show amplification of the inlJ and inlC genes. However, all seven clinical strains were positive for internalin genes. Furthermore, a multiplex PCR assay was employed to evaluate the major L. monocytogenes genoserogroups' distribution. The results revealed that the serotypes of lineage II are most frequently present in clinical and food isolates. In summary, PCR screening for both the major L. monocytogenes serovars and virulence genes revealed the potential public health risk posed by L. monocytogenes in aquatic products. Highlights: Molecular characterization of Listeria monocytogenes isolated from seafood products. Listeria spp. was present in 8.95% of retail products. The prevalence of L. monocytogenes was 2.9% in raw fish and RTE seafood samples. All clinical and six food strains were positive for four virulence marker genes.